Ultimate Functional Preservation With Intersphincteric Resection for Rectal Cancer - Collard, Maxime; Lefevre, Jérémie H. (Frontiers in Oncology, 2020)
Intersphincteric resection (IR) indications are not a clear-cut issue. An overly extreme attitude towards IR indications is dangerous because it may affect the oncological survival of patients on the one hand and lead to an unacceptable functional result on the other. The effectiveness of neoadjuvant radiochemotherapy makes patient selection even more complex. The objective of this work was therefore to take stock of the right indications of IR in view of the data in the literature on the subject. We detailed the pretherapeutic explorations to select properly the good candidates, the surgical procedures and the oncological and functional results of this complex procedure. The benefit of intersphincteric resection to the patient is undeniable by optimizing the post-operative quality of life related to the preservation of anal continence. Thanks to a careful patient selection, this strategy is not just a compromise between quality of life and cancer treatment but represents an optimal oncological treatment for very low rectal cancer. Intersphincteric resection is a model of what surgery is expected to be in the 21st century: more and more effective on the disease, less and less damaging for the patient.